Loss of UFL1 drives chromosome instability and tumorigenesis of prostate cancer - Jimin Li; Fang Yang; Xiao Zhang; Liangfei Xu; Hui Zheng; Liu Liu; Xin Wan; Tao Xu; Guanmin Jiang; Hao Wang (Proceedings of the National Academy of Sciences, 2026)
Chromosomal instability (CIN) is a prevalent form of genomic instability in prostate cancer (PCa). However, its molecular mechanisms remain inadequately understood. This study demonstrates that reduced expression of UFM1-ligase 1 (UFL1) is commonly observed in PCa and correlates with elevated CIN rates. UFL1 deficiency results in severe mitotic defects, errors in chromosome segregation, and aneuploidy, thereby promoting malignant transformation. Mechanistically, UFL1 interacts with RNF20 and catalyzes its UFMylation, which enhances RNF20 binding to CEP192, facilitating its centrosomal localization and supporting mitotic spindle assembly. Additionally, downregulation of the microphthalmia-associated transcription factor (MITF) exacerbates PCa aggressiveness by suppressing UFL1 expression. These findings identify the MITF–UFL1–RNF20 axis as a critical regulator of spindle integrity and a potential therapeutic target in PCa.